The relationship of students' emotional intelligence and the level of their readiness for online education: A contextual study on the example of university training in Saudi Arabia - A. M. Alenezi (Russian State Vocational Pedagogical University, 2020)
Introduction. It is well known that the effectiveness of students' online education depends largely on their skills to interact with the digital educational environment. At the same time, there has been a marked shift in scientific publications from the traditional point of view about the priority of competency formation in students to use educational information and communication technologies on the other aspects of online education, including psychometric.The aim of this research was to investigate the influence of students' emotional intelligence on their preparedness for online learning programmes.Methodology and research methods. A questionnaire survey was employed as the main tool. In the course of the questionnaire survey, Emotional Intelligence Scale (EIS) and Online Learning Readiness Scale (OLRS) were used to measure the selected characteristics of students. The method of single-factor dispersion analysis ANOVA (analysis of variance) and t-test of equal dispersions were applied to process the obtained empirical data.Results and scientific novelty. 340 Saudi students, admitted into the Faculties of Pharmacy, IT, Sciences and Arts in Northern Border University (Arar), took part in the questionnaire. The sample of respondents was random; only 208 respondents fully completed the survey. The gender of students was considered as a key variable. It was revealed that the level of emotional intelligence in female students is higher than in their male fellow students, which ultimately caused the best readiness of girls for online training. The analysis of the survey data showed the variance between the measured respondents' characteristics depending on the area of specialisation. If compared with the Sciences and Arts students, the representatives of the Faculties IT and Pharmacy demonstrated higher level skills to undertake online training, more expressed skills of self-control and computer selfefficacy. The level of online communication self-efficacy, recorded among the respondents, was not so significant. However, the respondents of all four faculties demonstrated a high level of motivation for independent online learning activities. It was reliably established that a high level of emotional intelligence correlates with readiness for such forms of work.It was found out that students are not always able to clearly identify their educational needs on their own and to understand them without someone's assistance, new arsenal of educational tools, their adequate application and quality. In addition, the emotional attitude to online learning is very significant. Therefore, in order to make e-learning effective, it is appropriate to conduct pre-diagnostics, taking into account students' psychometric parameters, to identify students' expectations about the online courses and to assess own readiness for such training. According to the author of the current publication, pedagogical support of the process of formation and development of emotional intelligence and formation of students' skills to regulate their feelings should become an integral part of the curriculum to ensure the success of the learning process. The author identified the critical points of teaching staff activity, which may vary depending on the required scale of the pedagogical intervention and the specific direction of training.Practical significance. The research results can be useful for teachers and administrators of educational institutions engaged in the development and promotion of distance and blended learning.